Reconnaissance study on the stratigraphy and characteristics of eruption products associated with basaltic caldera in Raung volcano, East Java, Indonesia - Moktikanana, M. L. A. (2022)
As one of the most active volcanoes with significant eruptive impact in Indonesia, the Raung volcano shows a trace of the pre-historical devastating eruption as evidenced by the morphology of caldera at its summit. Our fieldwork revealed the occurrence of four pyroclastic fall deposits, two lava flows, ignimbrite, block and ash flow deposit, and lahar as the products of Raung eruption. There is evidence of Plinian phase eruption represented by layers of pumice fall without any significant time gap, which is uncommon for an andesitic-basaltic stratovolcano. Thin section observation on lava and the lithic fragment of block and ash flow deposits reveals that the composition of Raung volcanic products is mainly basalt consisting of plagioclase, clinopyroxene, olivine, and orthopyroxene as the primary crystal phases. Hornblende and biotite also compose pumice as a minor constituent. This evidence implies that Raung magmatism may potentially evolve long enough to produce such massive pumice fall deposits. © Published under licence by IOP Publishing Ltd.